Neural network design - Hagan, Martin T.; Demuth, Howard B.; Beale, Mark H. (Boston : PWS Pub., 1996)
This guide to neural networks includes worked problems in each chapter, and supporting software demonstrations. The authors of this work also developed the neural networks toolbox (for MathWorks) and the fuzzy systems toolbox.
Preface -- Introduction -- Neuron Model and Network Architectures -- Perceptron Learning Rule -- Signal and Weight Vector Spaces -- Linear Transformations for Neural Networks -- Supervised Hebbian Learning -- Performance Surfaces and Optimum Points -- Performance Optimization -- Widrow-Hoff Learning -- Backpropagation -- Variations on Backpropagation -- Associative Learning -- Competitive Networks -- Grossberg Network -- Adaptive Resonance Theory -- Stability -- Hopfield Network -- Epilogue.
Includes bibliographical references and index.
1
Keywords: Neural networks (Computer science)